Teachers' Ability in Compiling Merdeka Curriculum-Based Teaching Modules in Kindergarten in Klojen District, Malang City (Case Study at BA Restu 1 Malang, Taman Indria 1 Malang Kindergarten, and ABA 9 Malang Kindergarten) - Carissima, Putri; Sutama, I Wayan; Astuti, Wuri (Universitas Negeri Malang, 2024)
This study aims to describe the ability of kindergarten teachers in compiling teaching modules based on the Merdeka Curriculum located in Klojen District, Malang City, along with the inhibiting factors and supporting factors. This study uses a descriptive qualitative type with a case study approach. The data source use the teaching module along with the results of interviews with 1 teacher from 3 kindergarten. The data collection techniques use the interviews, observations, and documentation. The study result show that the ability of teachers to compile teaching modules at BA Restu 1 Malang, Kindergarten Taman Indria 1 Malang, and Kindergarten ABA 9 Malang is included in the sufficient category because the inhibiting factors experienced by teachers include teaching modules require many attachments, different self-awareness of teachers, teaching modules content sometimes does not match the learning activities, and difficulties in determining appropriate learning media. The supporting factor that helps teachers include training to prepare teaching modules, free to cooperate with each other, and can prepare teaching modules according to the weekly program that has been made. This research cannot necessarily represent the ability of teachers in compiling teaching modules based on the Merdeka Curriculum because it is included in case study research. Keywords: Teacher Ability; Teaching Module; Merdeka Curriculum; Kidergarten